PENERAPAN EVIDENCE BASED NURSING TERAPI MUSIK PADA PASIEN DENGAN NYERI POST SECTIO CAESAREA DI RS BHAYANGKARA TK.I R. SAID SUKANTO - Husna Maharani, (2022)
Sectio caesarea causes discomfort experienced by a person because there is a wound in the incision area, causing pain. Pain can be treated with non-pharmacological therapy, one of which is music therapy. Music therapy is a nurse's independent action to address the patient's pain management. When listening to music, the body will release endorphins which have a function to restrain the transfer of pain impulses in the central nervous system so that pain is reduced. The instrument used to measure the pain scale in post sectio caesarea mothers is the Numeric Rating Scale (NRS). The results of the implementation after music therapy was carried out 1 time a day for 3 days were a decrease in the pain scale in post sectio caesarea patients. The conclusion of this study is that music therapy has an effect on post sectio caesarea pain. Patients who have performed sectio caesarea are advised to use music therapy as non-pharmacological therapy to reduce pain scale.